Thyroid function is not affected 6 or 24 hours after subcutaneous low molecular weight heparin - Mansour, Abbas Ali; Kadim, Hayder Qassim (Medical Studies/Studia Medyczne, 2017)
Introduction : There has been widespread use of low molecular weight heparin (LMWH) in medical and surgical practice over the years. Aim of the research : To see the effect of LMWH on thyroid function. Material and methods : a cross-sectional study was made of patients with acute coronary syndrome (ACS) admitted to the Faiha Hospital Coronary Care Unit (CCU) for the period from December 2014 to June 2015. We enrolled 70 patients, with no apparent clinical history or examination finding suggestive of thyroid disease. On admission for all, enoxaparin (4000–6000 units) was given subcutaneously once daily with other usual drugs used for ACS. Thyroid function test was done at baseline and after 6 h in 60 patients and after 24 h in 10 patients. Results : At the end of the study, we excluded three patients (TSH > 10 (1 patient) or TSH < 0.2 (2 patients)). So the total number of enrolled patients was 67; 57 patients were from the 6-hour group and 10 from the 24-hour group. Comparison between serum levels of thyroid hormones (TSH, free T4, total T4, and total T3) measured at time of admission, 6 h later in 57 patients and 24 h in 10 patients, showed no statistical difference in the level after low molecular weight heparin (enoxaparin) except for lower total T4 after 6 h (9.2 ±1.8 vs. 8.8 ±1.8 μg/dl, p = 0.003). Conclusions : Single-dose low molecular weight heparin (enoxaparin) given subcutaneously had no effect on thyroid hormone levels 6 or 24 h later in patients with ACS.